Practical Instructions with Content Differentiation to Improve Elementary School Students' Science Process Skills - Sari, Made Nirmala Karunika; Suarjana, I Made; Tegeh, I Made (Jurnal Pedagogi dan Pembelajaran, 2024)
Science process skills are abilities that students must have in order to be able to achieve learning goals through direct experience. Science process skills are obtained from theoretical and practical science learning. However, unfortunately learning activities are still carried out using lecture and practice methods which can improve science process skills and have not been carried out optimally. Practical activities are not equipped with practical instructions. The practical instructions used in schools only use the teacher's book so they do not accommodate all students' learning styles. Based on these problems, the aim of this research is to develop practical instructions with nuanced content differentiation to facilitate practical activities. The practical instructions for nuanced content differentiation have descriptive explanations and video explanations that are scanned using a QR-Code. This development research uses a 4D development model which consists of the stages of definition, planning, development and dissemination. The subject of this research is practical instructions. The data collection method uses observation sheets. The practical instructions that have been created have been tested for validity, practicality and effectiveness before they can be used in the classroom as a medium to support practical activities. The test results show that practical instructions with nuanced content differentiation are feasible and practical to use during practice. Practical instructions are effective in improving students' science process skills. Therefore, it can be concluded that the practical instructions developed are feasible, practical and effective for use in practical activities.